Experiential constructions in Yucatec Maya : a typologically based analysis of a functional domain in a Mayan language - Verhoeven, Elisabeth (Studies in language companion series, 2007)
This book combines a fieldwork-based language-specific analysis with a typological investigation. It offers a detailed and comprehensive analysis of the form and semantics of experiencer constructions in Yucatec, the Mayan language of the Yucatecan peninsula in Mexico. Since the linguistic expression of experience is not restricted to a specific grammatical area the study touches a great variety of grammatical fields in the language such as argument structure, grammatical relations, possessive constructions, subordinate constructions, etc. The empirical analysis of the Yucatec data is preceded.